2016
DOI: 10.4314/jae.v20i2.16
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change Information Needs of Rural Farmers in Enugu State.

Abstract: The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 3 publications
4
9
0
Order By: Relevance
“…Also the group of people who bears much of the burden of its impacts is rural farmers, who practice rainfed agriculture and hence depend on adequate rainfall for good crop yield (Okoro, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also the group of people who bears much of the burden of its impacts is rural farmers, who practice rainfed agriculture and hence depend on adequate rainfall for good crop yield (Okoro, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Also, people living in climate sensitive areas are most in need of access to climate information and support service. Such group of people in those areas are yet to experience the full benefits of climate research; information and support services to enable them effectively cope and build adaptive capacity to the changing climate (O'Brien, Sygan, Kingamlono and Hochobeb, (2008) in Okoro (2012)). Cherotich, Saidu and Bebe (2012) expressed that information sharing among climate change actors in Africa is limited and may be worse in semi-arid environments due to barriers like poverty, lack of infrastructure, illiteracy and socioeconomic factors.…”
Section: Introductionmentioning
confidence: 99%
“…This has serious implications on the level of knowledge respondents will have on recent trends about climate change and likewise hinder effective adaptation strategies by farmers. Okoro (2012) in his study found that the majority of farmers' information on climate change was by personal observation. Climate change and its uncertainties demand that farmers have regular access to new knowledge.…”
Section: Gender Differences In Knowledge Of Climate Change On Livestomentioning
confidence: 99%
“…In Enugu State Nigeria, [50] identify poor extension services and infrastructure as the major challenges to effective communication of climate change information to farmers. Nigerian media has not given adequate and efficient information on climate change issues to farmers [51].…”
Section: Carbon-smartmentioning
confidence: 99%